First Language Acquisition in a Three-Year-Old Child: A Phonological, Morphological, and Syntactic Analysis - Atika Zikri; Siti Ainim Liusti; Agustina Agustina (Srawung: Journal of Social Sciences and Humanities, 2026)
This study investigates the first language acquisition of a three-year-old Indonesian-speaking child at the phonological, morphological, and syntactic levels of linguistic analysis. Despite the considerable body of research on early childhood language development, naturalistic acquisition studies focusing on Indonesian as a first language remain underrepresented in the cross-linguistic literature, leaving a gap in understanding of how developmental patterns documented in widely studied languages manifest in typologically distinct ones. This study employed a qualitative descriptive design, with data collected over three weeks through participatory naturalistic observation within the subject's habitual domestic environment. The research subject was selected through purposive sampling on the basis of age, monolingual Indonesian language background, and absence of documented developmental disorder. Data were analysed following the interactive model of Miles, Huberman, and Saldaña, comprising the stages of data condensation, data display, and conclusion drawing. The findings reveal three principal outcomes. At the phonological level, the subject consistently substituted the trill consonant /r/ with the lateral approximant /l/ and the alveolar fricative /s/ with the palatal affricate /c/, patterns that are developmentally normative and consistent with universal consonant acquisition hierarchies. At the morphological level, the subject demonstrated productive use of base lexical forms across multiple word classes, alongside emerging but grammatically incomplete use of verbal prefixes. At the syntactic level, the subject produced all four major sentence types, with declarative sentences occurring most frequently, followed by interrogative, imperative, and exclamatory forms. These findings extend the cross-linguistic evidence base for universalist accounts of early language development and offer practical implications for parents and early childhood educators in supporting children's linguistic growth during this critical developmental period.